Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1088/2041-8205/777/1/l14
|View full text |Cite
|
Sign up to set email alerts
|

Massive Black Hole Pairs in Clumpy, Self-Gravitating Circumnuclear Disks: Stochastic Orbital Decay

Abstract: We study the dynamics of massive black hole pairs in clumpy gaseous circumnuclear disks. We track the orbital decay of the light, secondary black hole M •2 orbiting around the more massive primary at the center of the disk, using N -body/smoothed particle hydrodynamic simulations. We find that the gravitational interaction of M •2 with massive clumps M cl erratically perturbs the otherwise smooth orbital decay. In close encounters with massive clumps, gravitational slingshots can kick the secondary black hole … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
127
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 88 publications
(144 citation statements)
references
References 37 publications
15
127
1
Order By: Relevance
“…The latter produces a highly inhomogeneous, multiphase background, affecting the orbital decay by making it stochastic, and often leading to a much longer decay timescale (Figure 1). This general outcome confirms the findings of Fiacconi et al (2013), who used a simple constant-cooling model and had no star formation, BH accretion, nor feedback processes implemented. The degree of clumpiness, however, depends on the specific physics implemented in the runs.…”
Section: Orbital Decaysupporting
confidence: 86%
See 4 more Smart Citations
“…The latter produces a highly inhomogeneous, multiphase background, affecting the orbital decay by making it stochastic, and often leading to a much longer decay timescale (Figure 1). This general outcome confirms the findings of Fiacconi et al (2013), who used a simple constant-cooling model and had no star formation, BH accretion, nor feedback processes implemented. The degree of clumpiness, however, depends on the specific physics implemented in the runs.…”
Section: Orbital Decaysupporting
confidence: 86%
“…Indeed, our clumps are generally more compact and much denser than the typical GMC in the disk of the Milky Way. Despite the richer physics of the simulations presented here, the sizes and densities of the clumps are similar to those found in Fiacconi et al (2013), for which it was shown that a good match exists with clouds in the Galactic Center region (Oka et al 2001), which, albeit less extreme, represents an environment with high gas densities and stronger stellar radiation background more akin to what one expects in the nucleus of a merger remnant, which is what our CND model should capture. We repeated the same comparison here ( Figure A4).…”
Section: Summary and Discussionsupporting
confidence: 56%
See 3 more Smart Citations